4 siblings engineers from UMP - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 6 November 2022 – The apple doesn’t fall far from the tree, an apt expression for Afiq Aizzat Zamani, 23, the youngest child of Zamani Jamil, 63 and Nor Maslina Abd Manap, 57, who received a degree in B.Eng (Hons.) Mechanical Engineering at the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony.